Review of the impact of Productive Safety Net Program (PSNP) on rural welfare in Ethiopia - Gashaw Desalegn; Seid Nuru Ali (University of Bonn, Center for Development Research (ZEF), 2018)
This article reviews the empirical literature on the impact of the Productive Safety Net Program (PSNP) on different welfare outcomes of rural households in Ethiopia. The main finding of the review is that the PSNP had in general positive impacts on some attributes. PSNP has been found to have positive impacts on the food security of households, increasing crop yield and households' income. It has also been found to impact welfare in the form of improved health and school attendance, higher rates of insurance uptake, and improved cognitive skills in children. However, there is scant evidence on how much PSNP has protected or mitigated the possible deterioration in the purchasing power of beneficiaries after shocks such as drought and food price spikes. There is one exception to this literature gap, which showed that PSNP had a role in mitigating the adverse impact of inflation on the cognitive skills of children. In the face of declining land to labour ratio, increasing population, changing climate and environmental challenges, an important issue that needs to be addressed through research is the impact of PSNP on the longer-term perspective of agricultural transformation in Ethiopia. Furthermore, an implicit assumption in almost all major studies in the country in relation to social protection interventions such as PSNP is that, rural agricultural households can make a better livelihood within the framework of agriculture. A process of rural transformation requires engagement of households in side-line activities such as cottage industry, small scale manufacturing and services activities. Investigating the role of PSNP in this regard might be useful.
Keywords: H5; H7; I38; 330; productive safety nets programs; Ethiopia; welfare; food and nutrition security; price shocks